2020
DOI: 10.1016/j.ijid.2020.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Role of empiric treatment in hospitalized patients with Xpert MTB/RIF-negative presumptive pulmonary tuberculosis: A prospective cohort study

Abstract: The ability of clinical algorithms to identify tuberculosis disease and the impact of empiric treatment on survival in people with a negative Xpert MTB/RIF (Xpert) result remains poorly documented. Methods: Hospitalized Xpert-negative patients (125 initiated on empiric tuberculosis treatment based on a clinical algorithm and 125 in whom tuberculosis treatment was not started) were enrolled. Sputum samples were evaluated for Mycobacterium tuberculosis by culture. All study participants were followed up for 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Two observational studies from sub-Saharan Africa suggested that empirical TB treatment may reduce mortality in smear-negative inpatients; however, these were both conducted prior to the availability of Xpert [ 20 , 21 ]. An Ethiopian study of Xpert-negative hospitalized patients (21% HIV-positive) found substantial overtreatment but no differences in survival [ 22 ]. Data from outpatients have also reported widespread empirical TB treatment despite good availability of Xpert, but similar clinical outcomes, including mortality, between empirically treated and microbiologically confirmed TB patients [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two observational studies from sub-Saharan Africa suggested that empirical TB treatment may reduce mortality in smear-negative inpatients; however, these were both conducted prior to the availability of Xpert [ 20 , 21 ]. An Ethiopian study of Xpert-negative hospitalized patients (21% HIV-positive) found substantial overtreatment but no differences in survival [ 22 ]. Data from outpatients have also reported widespread empirical TB treatment despite good availability of Xpert, but similar clinical outcomes, including mortality, between empirically treated and microbiologically confirmed TB patients [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This analysis is a secondary analysis of a cohort study that aimed to determine the role of empiric treatment among hospitalized adults (age ≥ 18 years) with symptoms of pulmonary TB (current cough, night sweats, fever, and weight loss) who could produce a sputum sample and tested negative on the Xpert MTB/RIF assay 24 . For the cohort study, all consecutive hospitalized Xpert MTB/RIF-negative patients were followed to determine if they were started on TB treatment.…”
Section: Methodsmentioning
confidence: 99%
“…This analysis is a secondary analysis of a cohort study that aimed to determine the role of empiric treatment among hospitalized adults (age ≥ 18 years) with symptoms of pulmonary TB (current cough, night sweats, fever, and weight loss) who tested negative on the Xpert MTB/RIF assay [21]. The cohort study enrolled 125 patients treated empirically for active TB and 125 patients in whom the physician decided not to treat for TB.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%